Characteristics of an atrazine degrading bacterium and the construction of a microbial agent for effective atrazine degradation - Zhu, Jiangwei; Fu, Li; Meng, Zili; Jin, Caihua (Water and environment journal : WEJ, 2021)
A bacterial strain, YQJ‐6, capable of highly degrading atrazine was isolated from soil. Strain YQJ‐6 was identified as Bacillus atrophaeus based on 16S rRNA and the analysis of morphology as well as physiological and biochemical characteristics. The optimal pH value and temperature for strain YQJ‐6 to grow and degrade atrazine were 7.0–7.5 and 30–40°C, respectively. The degradation rate of atrazine (50 mg/L) by strain YQJ‐6 reached approximately 99.2% in 7 days. Strain YQJ‐6 also had a high tolerance to atrazine and could tolerate at least 1000 mg/L atrazine. In addition, strain YQJ‐6 was successfully made into a microbial agent that is easy to commercialize and can be used to treat atrazine residues in soil. The microbial agent containing the strain YQJ‐6 achieved good experimental results. It is believed that strain YQJ‐6 can be used to control atrazine pollution.